Sweet Sorghum Ecotheology - Metafisika, Kartika; Lestari, Endang Gati; Istifhama, Lia (Proceedings of Annual Conference for Muslim Scholars, 2025)
This study examines the potential of Sorghum (Sorghum bicolor L.) in advancing Sustainable Development Goals (SDGs), specifically food security (SDG 2) and climate action (SDG 13). Despite its resilience to drought and carbon sequestration capabilities, market challenges often deter farmers from its cultivation. This research explores a contrasting phenomenon led by a female activist in Lamongan, Indonesia, who successfully developed innovative downstream products from sorghum. Adopting a qualitative phenomenological approach, the study investigates the ecotheological expressions manifested in the activist’s lived experience and resilience. Findings reveal that her persistence is driven by a profound ecotheological ethics manifested in three forms: a spiritual conviction to steward the earth and nourish the community; innovative practices designed to maximize the plant's holistic "blessings"; and communal engagement to propagate these benefits. The study concludes that the internalization of spiritual-ecological values serves as a critical driver for sustainable small-scale agriculture and provides an authentic grassroots model for achieving the SDGs. Furthermore, the results highlight that strategic support from academic, governmental, and research institutions acts as a vital accelerator for such local initiatives.